SYSTEMIC MORPHOLOGICAL CHANGES ASSOCIATED WITH THE DYNAMICS OF PNEUMOCONIOSIS - Михайлова, Надежда Николаевна; Бугаева, Мария Сергеевна; Бондарев, Олег Иванович; Шавцова, Галина Михайловна (Medicine in Kuzbass, 2017)
Subject of the study. Systemic morphological changes associated with the dynamics of pneumoconiosis. Objective of the study – to study in the experiment the features of the development of morphological changes in the organs and tissues in the conditions of prolonged exposure to the coal-rock dust on the body. Methods. Experiments were carried out on white laboratory male rats of the experimental and control groups. The animals of the experimental group underwent inhalation exposure to the coal-rock dust of the gas fatty type in an average concentration of 50 mg/m3 for 12 weeks in the priming chamber. For histological examination of the morphological changes in the internal organs in the rats of both groups the fragments of the lungs, bronchi, heart, liver and kidneys at different periods of the experiment were taken. Main results. Prolonged inhalation of the coal-rock dust leads to the development of morphological disorders, primarily the bronchopulmonary system, as well as the heart, liver and kidneys. The changes are formed from the moment of the impact of the damaging factor on the body and are characterized by phase development. The pneumoconiotic process is accompanied by the progressive development of microcirculatory disorders and the same type of pathological changes in the vessel walls of all organs under investigation, the extent of which is associated with the duration of exposure to coal-rock dust on the body. Area of application of the results. The results of the conducted studies broaden and deepen the understanding of the mechanisms of pneumoconiosis development. Defining the stages of morphological changes has theoretical and practical meaning for elaboration of the recommendations for determining the timing and methods of prevention and correction of disturbances caused by exposure to the coal-rock dust. Conclusions. New data have been obtained that indicate a systemic exposure to the coal-rock dust on the morphological state of the organs and tissues of the body.